Headache-related health resource utilisation in chronic and episodic migraine across six countries. Issue 12 (29th June 2013) - Sanderson, Joanna C; Devine, Emily B; Lipton, Richard B; Bloudek, Lisa M; Varon, Sepideh F; Blumenfeld, Andrew M; Goadsby, Peter J; Buse, Dawn C; Sullivan, Sean D
Abstract : Objective: To describe headache-related health resource usage in chronic and episodic migraine across six countries. Methods: A web-based questionnaire eliciting data on several topics, including health resource usage, was administered to panellists with migraine from the USA, Canada, UK, Germany, France and Australia. Respondents were grouped into episodic and chronic migraine, based on reported headache phenotype and headache-day frequency. ORs were calculated, comparing usage in each country to that in the US, controlling for chronic versus episodic migraine and other factors. Results: Relative to the USA, the odds of visiting a provider for headache during the preceding 3 months were significantly higher in all countries, except Germany. Respondents in France were more likely to report having a provider they typically visited for headache-related care. The odds of visiting the emergency department for headache were significantly lower in France, the UK and Germany, and hospitalisation for headache was significantly more frequent in Canada and Australia. Respondents from all countries, except Canada, were more likely to report currently using a prescription-acute treatment, and those from France were more likely to report trying more than three acute treatments. Preventive treatment use did not differ significantly. Conclusions: Headache-related resource usage differed significantly between the USA and other countries. US respondents were generally less likely to report recent provider visits and use of prescription-acute treatments. They were more likely to report emergency department visits than in European countries, but less likely to report hospitalisation than in Canada and Australia.